Applications of bacteriophages against intracellular bacteria. (4th March 2022) - Śliwka, Paulina; Ochocka, Marta; Skaradzińska, Aneta
Abstract: Infectious diseases pose a significant threat to both human and animal populations. Intracellular bacteria are a group of pathogens that invade and survive within the interior of eukaryotic cells, which in turn protect them from antibacterial drugs and the host immune system. Limited penetration of antibacterials into host cells results in insufficient bacterial clearance and treatment failure. Bacteriophages have, over the decades, been proved to play an important role in combating bacterial infections (phage therapy), making them an important alternative to classical antibiotic strategies today. Phages have been found to be effective at killing various species of extracellular bacteria, but little is still known about how phages control intracellular infections. With advances in phage genomics and mechanisms of delivery and cell uptake, the development of phage-based antibacterial strategies to address the treatment of intracellular bacteria has general potential. In this review, we present the current state of knowledge regarding the application of bacteriophages against intracellular bacteria. We cover phage deployment against the most common intracellular pathogens with special attention to therapeutic and preventive strategies.